Structure and an unstable business operating environment: Revisiting burns and stalker’s organisation-environment theory in zimbabwe’s manufacturing sector - Sibindi, N; Samuel, O.M (AOSIS (pty) Ltd, 2019)
Background: Turbulent socioeconomic contexts coupled with volatile political environments pose a serious survival threat to business organisations. Complex operational environment of this dimension most often resists application of conventional management theories and practices. Organisational managers are therefore constantly challenged to adopt contingency strategies that will not only keep their organisations afloat, but also entrench competitive advantage that could effectively sustain operations. Aim: To update Burns and Stalker’s theory on structure and business environments. Setting: The dynamics of the Zimbabwe’s economy has assumed an extraordinary proportion of complexity due to intractable political instability and hostile economic environment. Methods: Using a survey research design and employing quantitative research strategy, this article examines the underlining propositions that defined the seminal work of Burns and Stalker regarding strategy adoption by organisations in a dynamic operating environment. Primary data was collected from 189 randomly selected managers in 350 manufacturing firms operating in Zimbabwe using a structured questionnaire. Data were analysed using structural equation modelling. Results: The major finding of the present study suggests that firms adopt a hybrid structure when confronted with an unstable operating environment. Conclusion: The finding is inconsistent with that of Burns and Stalker, who concluded that firms adopt organic structure in an unstable operating environment. While Burns and Stalker’s study was conducted in a relatively stable socioeconomic context, the present study was conducted in an operating environment that is characterised by turbulent socioeconomic and political instability. These environmental divergences could have influenced the outcome of both studies. © 2019. The Authors.
South African Journal of Economic and Management Sciences
Keywords: Burns and Stalker; Competitive advantage; Contingency approach; Mechanistic structure; Organic structure; Organisational structure; Political instability; Underdeveloped economies; Unstable operating environment